O uso da informação contábil no setor sucroalcooleiro: um estudo nas indústrias de Alagoas - Lima, Márcia Maria Silva de (2006)
This study has the purpose of discussion and reflection of how the accounting information in the managemental area are used by the sugar & alcohol industry, located at State of Alagoas, aiming to identify if them please their managers expectations in the process of taking decision. Ahead of an existent universe of 27 (twenty seven) companies registered at the Sugar & Alcohol Labor Union of State of Alagoas SINDAÇUCAR files, were collected 14 (fourteen) questionnaires to support the current research classified as explorative and descriptive. The junction of these two kinds of research resulted in a quantitative and perceptive analysis of the use of the accounting information in the process of taking decision of the Sugar & Alcohol industry in Alagoas. The results demonstrated in this research indicate that, although the managers consider relevant the information at cost area, they do not use them in the process of taking decision. The reports emitted by accountancy are only financial, such as balance sheets, income statement, financial flow, among others factors. The importance order that the managers give to the accounting information and the kind of information that they use in the process of taking decision do not indicates that they use the accountancy in administration level. The statistics analysis of the files collected allows infer that the information provided by accountancy are considered important, however are few used at the manager process